Philosophy in Context: Learning Experiences of Language and Translation Students in Libya - Sami Barkah; Salem Aladi (PT. Pusmedia Group Indonesia, 2026)
This study examines the students’ experiences, expectations, and perceptions of philosophy courses which is taught in non-philosophy major programs at the Faculty of Languages and Translation, University of Zawia, Libya. By using a mixed-methods research design, quantitative data were collected through a structured questionnaire administered to 250 undergraduate students from departments of English, French, Arabic and Italian languages. Qualitative insights were obtained from semi-structured interviews with 20 participants. The questionnaire was analyzed using descriptive statistics (frequencies, percentages, means, and standard deviations), while interview transcripts were examined through thematic analysis to generate and triangulate key themes. The findings show that although students recognize philosophy as intellectually and ethically valuable, they consistently perceive it as abstract, demanding, and insufficiently connected to their academic specialization in language and translation studies. A notable gap emerges between students’ high expectations, particularly regarding critical thinking, ethical awareness, and practical relevance, and their actual learning experiences. Challenges related to conceptual complexity, philosophical language, teaching pace, and assessment methods were prominently reported. However, qualitative evidence indicates that students stay positively disposed toward philosophy and express strong willingness to engage with the subject when instructional barriers are reduced. The study argues that these challenges came primarily from pedagogical and curricular disintegration rather than from students’ rejection of philosophy itself. The paper concludes by offering context-sensitive pedagogical implications for teaching philosophy to non-specialists in Libyan higher education, emphasizing the need for applied, student-centered, and interdisciplinary approaches. These findings imply that philosophy courses for non-specialists in Libyan higher education should be redesigned through stronger curriculum integration with language and translation programs, student-centered instruction, and assessment formats that emphasize applied reasoning rather than memorization.